Effect of proline on seed germination indices of Castile Sugar beet seeds under drought stress - Hamideh Ghafari; Mahmoud Reza Tadayon (علوم و فناوری بذر ایران)
Environmental stress, especially drought stress, can play an important role in the reduction of the plant growth stage, specifically during germination. To explore the germination mechanism of drought-stressed germination indices of sugar beet improved by exogenous proline, an experiment was conducted in factorial randomized complete design with four replications in laboratory, Faculty of Agriculture, University of Shahrekord in 2016. In this experiment, treatments included five levels of drought treatments (distilled water,-2,-6,-10 and-14 bar) and seed soaking with Proline (0 (control), 5 and 10 mM. Results indicated that germination percent, coefficient of velocity of germination, relative germination and seed length and weight vigor index of sugar beet seeds significantly decreased under drought stress, while increased mean germination time and allometry coefficient. Soaking with exogenous proline improved the germination percent, coefficient of velocity of germination, relative germination and seed length and weight vigor index of sugar beet under drought stress. Moreover, application of 10 mM proline decreased mean germination time and allometry coefficient 10 and 25% as compared to the control, respectively. In a word, soaking with proline could effectively alleviate the inhibitory effects of drought stress on sugar beet seed germination.